Antitrust Enforcement and Standard Essential Patents Moving beyond the FRAND Commitment - Tsilikas, Haris (Munich Intellectual Property Law Center - MIPLC, 2017)
The present thesis discusses the implications of the enforcement of standard-essential patents (SEPs) for competition law. Formal standard setting has the potential to result in near-optimal investment in research and development and at the same time in rapid implementation of innovative standards.